Investigation of steady state problems via quarter sweep schemes - Ng, Yit Hoe; Mohammad Khatim Hasan, (Universiti Kebangsaan Malaysia, 2013)
Numerical application helps researchers in simulating various problems and used for solving partial differential equation. Half sweep and quarter sweep approach have been applied onto iterative method to gain approximation solution. In this paper, the implementation of full sweep successive over relaxation (FSSOR), half sweep successive over relaxation (HSSOR) and quarter sweep successive over relaxation (QSSOR) methods and full sweep accelerated over relaxation (FSAOR), half sweep accelerated over relaxation (HSAOR) and quarter sweep accelerated over relaxation (QSAOR) for its numerical engines are shown. QSSOR and QSAOR method was the fastest among FSSOR, HSSOR, FSAOR and HSAOR methods. Additionally, QSAOR performance is more accurate than QSSOR.